Spot Localization Using PHY Layer Information - Sen, Souvik; Radunovic, Bozidar; Choudhury, Romit Roy; Minka, Tom (In proceedings of ACM Mobisys, 2012)
This paper explores the viability of precise indoor localization using physical layer information in WiFi systems. We find evidence that channel responses from multiple OFDM subcarriers can be a promising location signature. While these signatures certainly vary over time and environmental mobility, we notice that their core structure preserves certain properties that are amenable to localization. We demonstrate these ideas through a functional system called PinLoc, implemented on off-the-shelf Intel 5300 cards. We evaluate the system in an active engineering building, a busy student center, a cafeteria, and at the Duke University museum, and demonstrate localization accuracies in the granularity of 1m x 1m boxes, called spots. Results show that PinLoc is able to localize users to a spot with 90% mean accuracy, while incurring less than 6% false positives. We believe this is an important step forward, compared to the best indoor localization schemes of today, such as Horus.